Increasing student learning through multimedia projects - Simkins, Michael, 1948- (Association for Supervision and Curriculum Development, 2002)
* How do I organize project-based learning in my classroom? * How do I ensure projects address curriculum standards? * What can I do to maximize the benefits my students get from using technology? * How do I prevent technology problems from eclipsing learning goals? This book answers teachers' questions about enhancing student achievement through project-based learning with multimedia.